تأثير المستخلصات المائية لبعض نباتات العائلة الصليبية في نمو بعض فطور التربة - طباش, سمير; المغربي, صباح; حوش, ماري (Latakia University Journal -Biological Sciences Series, 2019)
أجريت دراسة مخبرية لمعرفة تأثير المستخلص المائي للبقايا الجافة لنباتات الفجل و الكرنب و الملفوف عل نمو وتطور الفطور Fusarium oxysporum , Sclerotinia sclerotiorum , Botrytis cinerea , Trichoderma sp. . حيث استخدمت التراكيز 0.1 , 0.2, 0.4% وكانت المستخلصات الثلاثة فعالة في تثبيط نمو الفطور المدروسة وكان التركيز 0.4% هو الأكثر فاعلية على جميع الفطور المستخدمة في الاختبارات . تأثر الفطر فيوزاريوم بالمستخلص المائي للفجل والكرنب حيث بلغ قطر المستعمرة الفطرية عند التراكيز الثلاثة مع مستخلص الفجل35.5, 44.4 , 44.4 % ومع مستخلص الكرنب 63.1 , 81.5 , 68.4 % في حين تأثر الفطران بترايتس و سكليروتينيا بالمستخلصات المائية للفجل والكرنب والملفوف عند التركيز 0.4 % حيث كان قطرالمستعمرة عندها للبترايتس 53 , 43.2 , 77.6 % على التوالي وقطر المستعمرة للسكليروتينيا عندها 24.7 , 38.1 , 71.4 % على التوالي . تأثر الفطر تريكودرما بمستخلصي الفجل والكرنب اللذين ثبطا نموه عند التركيز 0.4% حيث كان قطر المستعمرة عنده 44.7 , 42.3 % على التوالي . Laboratory experiments were conducted to study the effects of aqueous extracts of some cruciferous dried plant residues (cabbage, radish, caulorapa) on some soil fungi (Fusarium oxysporum , Botrytis cinerea , Sclerotinia sclerotiorum , Trichoderma sp.) at the concentrations 0.1, 0.2, 0.4 %. The three plants prevented fungi growth especially at the 0.4% concentration which was the most effective on the growth of all studied fungi. Fusarium was affected by radish and caulorapa at the concentrations 0.1, 0.2, 0.4%; with radish, the percentages of growth were 35.5, 44.4, 44.4 % in succession , and with caulorapa were 63.1, 81.5, 68.4 % in succession .Botrytis and sclerotinia were affected by radish, caulorapa, and cabbage at the concentration 0.4%;the percentages of growth of Botrytis were 53, 43.2, 77.6% in succession, and the percentages of growth of Sclerotinia were 24.7, 38.1, 71.4% in succession. Trichoderma was affected by radish and caulorapa only which obviously prevented growth at the concentration 0.4%, and the colony diameters were 44.7, 42.3% in succession.